Sweden now 1982-II_2 - Testologen Ltd. (IMU-Testologen AB, 1986)
In this survey the questions about life style, decisional power at work and reading style have been removed.

Subset of Sweden now 1982-II, covering the period 1982-01-21 to 1982-03-11

In this survey the questions about life style, decisional power at work and reading style have been removed.

Delmängd av ORVESTO1982-II som omfattar perioden 1982-01-21 till 1982-03-11
ORVESTO 1982-II_2
Sverige nu 1982-II
Keywords: consumption; konsumtion; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; shopping; shopping; retail outlets; försäljningsställen; domestic appliances; hushållsapparat; consumer goods; konsumtionsvaror; membership; medlemskap; interest (cognitive processes); intresse (kognitiva processer); Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap